Psychological skills of Iraq fencing clubs’ players aged 17 and above for the central and southern regions - Ghadhban , Ali; Farhoud , Nedaa (Journal of Physical Education, 2025)
The aim of the research is to study the reality of psychological skills among fencing players aged 17 and above for the central and southern regions for the 2022-2023 season. The researchers used the descriptive method (survey method) to suit the nature of the research problem, and the community is represented by the players of Iraq clubs to duel for the central and southern regions for the 2022-2023 season, which number (111) players The researchers used the questionnaire to collect the necessary data to achieve the research goal by building and applying a psychological skills scale aimed at identifying the reality of psychological skills among fencing players, and the most important findings of the researchers were that the reality of psychological skills among fencing players came statistically significant in general, which indicates that fencing players possess some psychological skills (self-confidence, motivation for achievement, concentration of attention) while some skills were not at the required level and did not achieve statistical significance (mental perception, relaxation, coping with anxiety, managing psychological stress) It turns out that fencing players have a weakness in these skills. The researchers recommend preparing special training programs for training in psychological skills by specialists in psychological counseling and guidance or subjecting trainers to courses to train psychological skills.